Identification of Economic Subsectors That Can Increase Among Covid-19 Pandemic - Wiwik Istyarini; Azizah Fitriani; Oktaviani Permatasari; Zenita Afifah Fitriyani (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
The Corona outbreak has hit various joints of the economy. The spread of the virus, which requires human activities to be carried out through social distancing (social distancing) and at an extreme level, taking lockdown steps will have an impact on slowing economic activity (supply and demand) This study aims to identify the economic subsector that can survive and even increase amid the COVID-19 pandemic. The method in this study uses the System Literature Review (SLR), by examining several sources used as material in searching and obtaining literature including articles, electronic media and the web. These sources are used as the basis for analyzing and drawing conclusions in making the results of the study. The results of the research on the identification of economic subsectors that can increase in the era of the COVID-19 pandemic show that the economic sectors that are able to survive and actually experience an increase in the midst of the COVID-19 pandemic are the agriculture , plantation, livestock, forestry and fisheries sectors. In terms of the subsector, the increase occurred in plantation crops driven by harvests in strategic plantation commodities including oil palm, cocoa and cloves. Then, the fisheries subsector is also projected to increase in line with decreasing rainfall that affects catches. Other economic sectors that are projected to survive are the electricity, gas and clean water sectors, as they are the basic needs of the community on a daily basis.